Perkembangan Teknologi Jaringan 5G di Indonesia - Muhamad Rizky; Selpi Amanda Fadillah; Juniwan Juniwan; Muhamad Yusuf Habibi; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The development of the world of telecommunications continues to improve. Its initial appearance was as first generation technology (1G) which still uses the same system. In 1991, 2G technology began to develop, using a digital system and being able to provide not only voice services but also data services. This technological development was then followed by 3G and 4G. Currently, technological progress has increased very rapidly in almost every field of technology. has created very sophisticated tools to support human work. One of the latest technological advances that plays an important role is the emergence of 5G technology. 5G technology is a wireless technology that is more complex than previous wireless technologies. With greater bandwidth, higher data speeds and lower latency, this technology can provide opportunities and benefits for operators to create new business models. Keywords: